(untitled) (In situ, 2024)
The ruins of a fortified medieval and post-medieval settlement important for Croatian historical and cultural heritage are situated at the location of Gradina in Vrana. During 2023, the fourth research campaign was carried out in the area located between the Gothic church and polygonal rampart with a slope, where several different layers were investigated, which were created as a result of the deliberate filling of the area and reinforcing the walls at the beginning of the Modern Period. The walking surface was unearthed, and in the western part also the stairs and an opening that were subsequently closed. Small archaeological finds can be dated from the 13th to the late 15th or early 16th century.